Pemodelan Jumlah Penduduk Miskin di Jawa Timur dengan Generalized Linier Model - Noviana Pratiwi; Maria Jefin Paput (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Poverty as a development issue is an important thing to pay attention. Therefore, it is necessary to analyze to prevent an increase in the number of poor people in an area, one of which is by considering the things that affect poverty estimates and knowing the model of the number of poor people that can later be used as predictions. East Java is the region in Indonesia with the highest population in Indonesia in 2019. One way to find out the influencing factors and at the same time to make a model of the number of poor people in East Java is by modeling with the Generalized Linear Model (GLM) method. General Linear Model (GLM). GLMs aim to determine the causal relationship and the influence of the independent variable on the dependent variable. The GLMs model in this study uses the Gaussian family because the research response variable (Y) is an integer. The results show that of the seven estimated models, only one model that meets the significance is the model with the dependent variable population density (X3). So it can be concluded that between Area (X1), Open Unemployment Rate (X2), and Population Density (X3), population density has a significant effect on the number of poor people with a 95% confidence level.